Motor cortical inhibitory deficits in patients with obsessive-compulsive disorder–A systematic review and meta-analysis of transcranial magnetic stimulation literature - Rodrigues da Silva, Daniel; Maia, Ana; Cotovio, Gonçalo; Oliveira, José; Oliveira-Maia, Albino J.; Barahona-Corrêa, J. Bernardo (Frontiers in Psychiatry, 2022)
Obsessive-compulsive disorder (OCD) is a highly prevalent chronic disorder, often refractory to treatment. While remaining elusive, a full understanding of the pathophysiology of OCD is crucial to optimize treatment. Transcranial magnetic stimulation (TMS) is a non-invasive technique that, paired with other neurophysiological techniques, such as electromyography, allows for in vivo assessment of human corticospinal neurophysiology. It has been used in clinical populations, including comparisons of patients with OCD and control volunteers. Results are often contradictory, and it is unclear if such measures change after treatment. Here we summarize research comparing corticospinal excitability between patients with OCD and control volunteers, and explore the effects of treatment with repetitive TMS (rTMS) on these excitability measures. We conducted a systematic review and meta-analysis of case-control studies comparing various motor cortical excitability measures in patients with OCD and control volunteers. Whenever possible, we meta-analysed motor cortical excitability changes after rTMS treatment. From 1282 articles, 17 reporting motor cortex excitability measures were included in quantitative analyses. Meta-analysis regarding cortical silent period shows inhibitory deficits in patients with OCD, when compared to control volunteers. We found no statistically significant differences in the remaining meta-analyses, and no evidence, in patients with OCD, of pre- to post-rTMS changes in resting motor threshold, the only excitability measure for which longitudinal data were reported. Our work suggests an inhibitory deficit of motor cortex excitability in patients with OCD when compared to control volunteers. Cortical silent period is believed to reflect activity of GABAB receptors, which is in line with neuroimaging research, showing GABAergic deficits in patients with OCD. Regardless of its effect on OCD symptoms, rTMS apparently does not modify Resting Motor Threshold, possibly because this measure reflects glutamatergic synaptic transmission, while rTMS is believed to mainly influence GABAergic function. Our metanalyses are limited by the small number of studies included, and their methodological heterogeneity. Nonetheless, cortical silent period is a reliable and easily implementable measurement to assess neurophysiology in humans, in vivo. The present review illustrates the importance of pursuing the study of OCD pathophysiology using cortical silent period and other easily accessible, non-invasive measures of cortical excitability.